Efficacy of Low-dose and High-dose Radioactive Iodine Ablation With rhTSH in Korean Patients With Differentiated Thyroid Carcinoma: The First Report in Nonwestern Countries. (August 2016) - Joung, Ji Young; Choi, Ji Hun; Cho, Yoon Young; Kim, Na Kyung; Sohn, Seo Young; Kim, Sun Wook; Chung, Jae Hoon
Abstract : Objective: The aim of this study was to confirm the equivalent efficacy of recombinant human TSH (rhTSH) and thyroid hormone withdrawal (THW) as used in the preparation for low-dose and high-dose radioactive iodine (RAI) ablation in Korean patients with differentiated thyroid carcinoma. Subjects and Methods: This retrospective study was designed to compare the efficacy of rhTSH and THW when used before ablation with low-dose (30 mCi) and high-dose (100 mCi) RAI, respectively. The study group included 570 patients with DTC with tumors staged T1 to T3, N0 to N1, and M0. Before RAI ablation, 190 patients used rhTSH and 380 patients matched by age, sex, T-stage, and N-stage used THW. The success of ablation was evaluated in each group based on 4 criteria: (1) stimulated thyroglobulin (sTg) <2 ng/mL, (2) sTg<2 ng/mL and negative diagnostic whole-body scan (DxWBS), (3) sTg<1 ng/mL, and (4) sTg<1 ng/mL and negative DxWBS. Results: When both sTg<2 ng/mL and negative DxWBS were selected as criteria for success in patients treated with low-dose RAI, the success rates were 80.5% and 77.0% with rhTSH and THW, respectively (95% confidence interval, 5.9-12.8). Using both sTg<1 ng/mL and negative DxWBS as criteria, success rates were 78.2% and 71.8% with rhTSH and THW, respectively (95% confidence interval, 3.6-16.2). Using any criteria for success, low-dose RAI ablation with rhTSH was as effective as THW. Similar results were found for high-dose RAI ablation in patients using either rhTSH or THW. Conclusions: Low-dose and high-dose RAI ablation were equally effective using either rhTSH or THW before ablation in Korean patients with DTC, respectively.